An unusual cause of hemoperitoneum: case report with review of literature. (2015) - Kumar, S; Khanna, S; Roy, A; Gupta, SK
Highlights: Spontaneous hemoperitoneum (SH) is a rare entity. The clinical presentation of isolated neurofibromatous lesions of the intestines are variable. In asymptomatic patient no treatment may be required and patient may be kept on follow up. Occasionally, they manifest with complications such as intestinal bleeding, obstruction or perforation. Surgery is the treatment of choice in symptomatic intestinal neurofibroma. Abstract: Spontaneous hemoperitoneum (SH) is a rare entity which can be life-threatening. Gastrointestinal neurofibromas are rare. Occasionally, such lesions may be the initial sign of NF1 in patients without any other clinical manifestations of the disease. The clinical presentations of isolated neurofibromatous lesions of the intestines are variable. In asymptomatic patient no treatment may be required and patient may be kept on follow up. Occasionally, they manifest with complications such as intestinal bleeding, obstruction or perforation. Surgery is the treatment of choice in symptomatic intestinal neurofibroma. We present the case of a 55 year-old male with acute abdomen due to rupture of isolated neurofibroma as one of the cause of SH. This case represents a rare presentation of isolated intestinal neurofibromatosis in a patient without systemic manifestations and highlights the need for high index of suspicion to exclude neurofibromatosis type 1 or multiple endocrine neoplasia type 2b.